Total Quality Management (TQM) at an original device manufacturer (ODM) a case study : failure analysis depertment - Ramanathan, Geeva Raj (2009)
The purpose of this write up is to execute and evaluate a case study implementation of Total Quality Management (TQM) philosophy at the Failure Analysis Department of an Original Device Manufacture (ODM). This is an implementation effort at a very technically inclined entity whereby the preimplementation and post-implementation evaluation highlights the main TQM elements that mainly influences the entity. Quantitative and non-quantitative assessments are used to assess the pre-implementation and post-implementation changes. Eventually, the implementation efforts are conceptualized. Based on the implementation, it was identified that Continuous Improvement, Employee Involvement, and Training and Education are the main TQM elements that influence the Failure Analysis Department in particular and the ODM in general.